Variability of rice yield with respect to crop health - Renny Eka Putri,; Yahya, Azmi; Adam, Nor Mariah; Abd Aziz, Samsuzana (Penerbit Universiti Teknologi Malaysia, 2016)
Chlorophyll content of leaf can be used as an indicator of the crop health. The SPAD chlorophyll meter has been acceptably used for rapid analysis of chlorophyll content and nitrogen status of crops while it has not been established how strongly the SPAD values are correlated with rice yield within a plot. This study was to explore the relationship between rice yields and the leaf SPAD value of the associated rice plots. Twenty sampling points of rice leaves plant were taken at three difference growing stages based on grid point sampling of 30m x 18m for two crop seasons. Two methods, namely instantaneous yield from on-board yield monitoring system mounted on a combine harvester and estimated crop yield from cutting test (CCT) yield were used to measure the variability of harvested rice yield within the rice plot. The SPAD values were found positively correlated with grain yield at different growth stages. The highest significant correlation was at crop age 70 days after planting with Pearson’s correlations (r) ranging 0.7280 to 0.8336 (P<0.001). Consequently, information with regards to SPAD value variability could triggers farmers in taking immediate in situ action for improving the crop yield while information with regards to crop yield variability could assist farmers in planning the proper farming practice for the subsequent cropping seasons. Generally, this available technology would assist farmers in improving their crop yield and their economic status.